2013
DOI: 10.1038/mp.2013.17
|View full text |Cite|
|
Sign up to set email alerts
|

The genome-wide supported microRNA-137 variant predicts phenotypic heterogeneity within schizophrenia

Abstract: We examined the influence of the genome-wide significant schizophrenia risk variant rs1625579 near the microRNA (miRNA)-137 (MIR137) gene on well-established sources of phenotypic variability in schizophrenia: age-at-onset of psychosis and brain structure. We found that the MIR137 risk genotype strongly predicts an earlier age-at-onset of psychosis across four independently collected samples of patients with schizophrenia (n=510; F1,506=17.7, P=3.1 × 10(-5)). In an imaging-genetics subsample that included addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 75 publications
1
75
3
Order By: Relevance
“…the relative anatomical or physiological strength of connections from either eye to individual cells in the primary visual cortex) and affects the maturation of dendritic spines (Mellios et al, 2011;Tognini et al, 2011). Thus, these studies showed for the first time a function of (Wright et al, 2016;Siegert et al, 2015;Lett et al, 2013) Idiopathic autism Multiple miRNAs (Wu et al, 2016;Mor et al, 2015;Mundalil Vasu et al, 2014) Fragile-X syndrome miR-9, miR-124 ) let-7b/c, miR-125a, miR-181a, miR-296, miR-342 (Wan et al, 2016 miR-125b, miR-132 (Edbauer et al, 2010) miR-125a (Muddashetty et al, 2011) miR-181d (Wang et al, 2015 Rett syndrome miR379-410 cluster and other miRNAs (Wu et al, 2010) let-7f (Mellios et al, 2014) miR132-212 cluster (Im et al, 2010) 377 miRNAs (e.g. miR-134, miR-383, miR-382, miR-182) (Cheng et al, 2014) miR-199a (Tsujimura et al, 2015) miRNAs in the activity-dependent maturation of neural circuits, a form of developmental synaptic plasticity, in the mammalian brain in vivo.…”
Section: Synapse Developmentmentioning
confidence: 73%
“…the relative anatomical or physiological strength of connections from either eye to individual cells in the primary visual cortex) and affects the maturation of dendritic spines (Mellios et al, 2011;Tognini et al, 2011). Thus, these studies showed for the first time a function of (Wright et al, 2016;Siegert et al, 2015;Lett et al, 2013) Idiopathic autism Multiple miRNAs (Wu et al, 2016;Mor et al, 2015;Mundalil Vasu et al, 2014) Fragile-X syndrome miR-9, miR-124 ) let-7b/c, miR-125a, miR-181a, miR-296, miR-342 (Wan et al, 2016 miR-125b, miR-132 (Edbauer et al, 2010) miR-125a (Muddashetty et al, 2011) miR-181d (Wang et al, 2015 Rett syndrome miR379-410 cluster and other miRNAs (Wu et al, 2010) let-7f (Mellios et al, 2014) miR132-212 cluster (Im et al, 2010) 377 miRNAs (e.g. miR-134, miR-383, miR-382, miR-182) (Cheng et al, 2014) miR-199a (Tsujimura et al, 2015) miRNAs in the activity-dependent maturation of neural circuits, a form of developmental synaptic plasticity, in the mammalian brain in vivo.…”
Section: Synapse Developmentmentioning
confidence: 73%
“…[75] strongly predicting an earlier age-at-onset of psychosis, reduced white matter integrity, and cognitive deficits in combination with higher severity of negative symptoms [84][85][86]. Moreover, two SNPs in the Dgcr8 and Dicer gene have been significantly associated with an altered schizophrenia risk in a Chinese schizophrenia patient cohort, suggesting that the specific genetic variants in miRNA machinery genes may affect the susceptibility to the disease [87].…”
Section: Mirnamentioning
confidence: 96%
“…MiRNAs are known to regulate multiple neurodevelopmental processes and several miRNAs regulate the expression of multiple genes relevant to neurodevelopmental disorders (Lett et al, 2013;Meza-Sosa et al, 2014). As an example, miRNA 124 and 195 are both implicated in autism, each modulating multiple targets and thus affecting several autism genes (Vaishnavi et al, 2013).…”
Section: The Need For Better Preclinical Data To Foster Novel Drug Thmentioning
confidence: 99%